2015
DOI: 10.1039/c5cp04563k
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical MP2 results on some hydrates of cytosine: binding sites, energies and the first hydration shell

Abstract: A detailed quantum chemical investigation was undertaken to obtain the structure and energetics of cytosine hydrates Cyt·nH2O, with n = 1 to 7. The MP2(fc)/aug-cc-pVDZ level was used as the standard, with some DFT (B3LYP) and coupled cluster calculations, as well as calculations with the aug-cc-pVTZ basis set added for comparison. In a systematic search for microhydrated forms of cytosine, we have found that several structures have not yet been reported in the literature. The energies of different isomers, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
(73 reference statements)
3
12
0
Order By: Relevance
“…A more thorough list of isomers and their structures is given in the Supporting Information. For Cy microhydrates, both G4MP2 and ωB97XD results are qualitatively consistent with previous theoretical studies regarding the stability order among various Cy·(H 2 O) n isomers. , The G4MP2 energies agree very well with the more accurate CCSD­(T)/aug-cc-pVTZ//ωB97XD/aug-cc-pVTZ results (see Table ), providing a good justification to use this efficient method for larger Cy clusters. Boltzmann populations of some important Cy monohydrates and dihydrates listed in Table were calculated with the Δ G s obtained from the G4MP2 results of all isomers listed in Figures S1 and S2, respectively.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…A more thorough list of isomers and their structures is given in the Supporting Information. For Cy microhydrates, both G4MP2 and ωB97XD results are qualitatively consistent with previous theoretical studies regarding the stability order among various Cy·(H 2 O) n isomers. , The G4MP2 energies agree very well with the more accurate CCSD­(T)/aug-cc-pVTZ//ωB97XD/aug-cc-pVTZ results (see Table ), providing a good justification to use this efficient method for larger Cy clusters. Boltzmann populations of some important Cy monohydrates and dihydrates listed in Table were calculated with the Δ G s obtained from the G4MP2 results of all isomers listed in Figures S1 and S2, respectively.…”
Section: Methodssupporting
confidence: 88%
“…For the hexahydrate (n = 6), the most stable isomer is the AABBCC-type that forms a three-dimensional cage-like structure along the Watson−Crick edge. A recent MP2(fc)/aug-cc-pVDZ study 38 predicted that the most stable isomers of both n = 5 and 6 microhydrates involve such cagelike structures. However, we found that, at the G4MP2 level, the pentahydrate isomer containing such a cage-like structure is much higher in energy than the most stable AABBC-type isomer (see Figure S5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also considered the influence of the cytosine binding process with graphene on the interaction of this cytosine with water molecules (the role of the solvation effects) limiting this consideration only the first hydration shell (ex., including only the strong bounded water molecules). There have been numerous quantum chemical calculation on the interaction between cytosine and water (see, for example,ref ). The number of water molecules may be up to seven water molecules that can bind directly to cytosine .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The number of water molecules may be up to seven water molecules that can bind directly to cytosine. 60 We determined the number of H-bonds formed by cytosine5 with water molecules at each step and showed their variation with time (Figure S6). This number of H-bonds was varied from 2 until 15 with time and the mean value was about 6−7 bonds (depending on the stacked cytosine number).…”
Section: Computer Simulation Of Cytosine Oligomer Adsorption Onmentioning
confidence: 99%